EFFECTIVENESS OF AUDIO-VISUAL LEARNING MEDIA ON MADRASAH STUDENTS’ UNDERSTANDING OF ISLAMIC CULTURAL HISTORY - Sugiyono Sugiyono; Suratman Suratman (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the influence of audio-visual media on students' understanding of Islamic Cultural History learning in madrassas in East Kalimantan Province. The study used an explanatory quantitative approach with a sample of 302 MTs and MA students, taken through proportional random sampling. The instrument is a Likert scale questionnaire that has been tested for validity and reliability. Data were analyzed using descriptive statistics and simple linear regression. The results showed that the use of audio-visual media had a positive and significant effect on student understanding, accounting for 29.3% of the variation in understanding. In conclusion, audio-visual integration strengthens student retention, engagement, and motivation to learn. The implications of this study indicate that integrating audio-visual media into Islamic Cultural History learning can improve students’ comprehension, engagement, and learning motivation in madrassas. These findings encourage educators to adopt technology-based instructional strategies that support interactive and student-centered learning environments. In addition, educational institutions and policymakers may use this evidence to strengthen digital learning infrastructure and teacher training programs. The study also implies that multimedia-assisted instruction can serve as an effective pedagogical approach for enhancing learning quality across various educational contexts.